2011
DOI: 10.1021/ja1113529
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamics and Time-Resolved Fluorescence of Azobenzene in Solution: A Mixed Quantum-Classical Simulation

Abstract: We have simulated the photodynamics of azobenzene by means of the Surface Hopping method. We have considered both the trans → cis and the cis → trans processes, caused by excitation in the n → π* band (S(1) state). To bring out the solvent effects on the excited state dynamics, we have run simulations in four different environments: in vacuo, in n-hexane, in methanol, and in ethylene glycol. Our simulations reproduce very well the measured quantum yields and the time dependence of the intensity and anisotropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
194
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(205 citation statements)
references
References 87 publications
10
194
0
1
Order By: Relevance
“…Absorption of a photon at 514 nm deposits an energy of hn ¼ 2.4 eV into a dMR azo core, enough to excite a single harmonic degree of freedomto T ¼ hn=k B ¼ 29,000 K. Some fraction of this energy appears in a form that locally tests the molecular orientational barrier distribution at the effective temperature of T CP B800 K. Fast spectroscopy [45][46][47] , quantum/molecular dynamic simulation 18,48 and molecular dynamic simulation 17 provide a semi-quantitative picture of this process, indicating that it is principally mechanical, with the photon energy appearing as a coherent force acting transiently on the environment of the absorbing molecule 49,50 , as follows. Upon photon absorption and electronic excitation, the azo core returns to the ground electronic manifold in a transition state configuration from which coherent change of the intra-molecular configuration takes place along one of several possible paths,for example, trans to cis or trans to trans, all of which reduce the internal potential energy by B2 eV (45 kcal per mole), representing almost all of the absorbed photon energy 18,48 .…”
Section: Sam Glassy Relaxation: Two Distinct Barrier-crossing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption of a photon at 514 nm deposits an energy of hn ¼ 2.4 eV into a dMR azo core, enough to excite a single harmonic degree of freedomto T ¼ hn=k B ¼ 29,000 K. Some fraction of this energy appears in a form that locally tests the molecular orientational barrier distribution at the effective temperature of T CP B800 K. Fast spectroscopy [45][46][47] , quantum/molecular dynamic simulation 18,48 and molecular dynamic simulation 17 provide a semi-quantitative picture of this process, indicating that it is principally mechanical, with the photon energy appearing as a coherent force acting transiently on the environment of the absorbing molecule 49,50 , as follows. Upon photon absorption and electronic excitation, the azo core returns to the ground electronic manifold in a transition state configuration from which coherent change of the intra-molecular configuration takes place along one of several possible paths,for example, trans to cis or trans to trans, all of which reduce the internal potential energy by B2 eV (45 kcal per mole), representing almost all of the absorbed photon energy 18,48 .…”
Section: Sam Glassy Relaxation: Two Distinct Barrier-crossing Processesmentioning
confidence: 99%
“…In this process the vibrational modes of the molecule are thermalized, with the energy ending up principally in the fully excited low-frequency vibrations and the molecule which reach an internal temperature of B1,100 K 45 . However, in solution nearly all of the energy of such a coherent change of molecular shape is released as orientational and translational work done on neighbouring molecules 18,47,48 . In particular, the detailed simulations of Tiberio et al 18 show that for azobenzene in solvent, changes in molecular shape are predominantly opposed by intermolecular viscous forces rather than by intramolecular dissipation, leading to a damped relaxation on a much longer time scale (B410 ps) than in vacuum, a dynamic to be expected (Supplementary Note 7) and confirmed by experiment 46 .…”
Section: Sam Glassy Relaxation: Two Distinct Barrier-crossing Processesmentioning
confidence: 99%
“…27,28,30,31,42,58 On-the-fly dynamics simulations were also performed for the photoisomerization of azobenzene on the basis of semiempirical molecular orbital calculations with the surface hopping method 29,33,55,59,61 and with the multiple spawning method. 32 Recently, ab initio molecular dynamics (AIMD) simulations at the CASSCF level 26,47,54,57 and Car-Parrinello molecular dynamics simulations 34,45,49,50 were also performed for the photoisomerization of azobenzene in nπ * excitation. In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The transition between the two isomeric states occurs via a number of intermediate excited states while several conformational degrees of freedom of the molecule change. 40,41 The situation is even more complicated when the isomerization occurs in a crowded environment because neighboring molecules then most likely interfere. 42 In our model the isomerization process is drastically simplified: it consists of a simple switch from the straight to the bent needle and vice-versa.…”
Section: A Molecular Modelmentioning
confidence: 99%